Effectiveness of the Deep Dialogue Critical Thinking Model on Elementary Students’ Social Studies Understanding - Shobirin, Syahril; Hanikah; Fadly, Aris (Papanda Publisher, 2025)
This study aimed to examine the effectiveness of the Deep Dialogue Critical Thinking (DDCT) learning model in improving fifth-grade students’ understanding of Social Studies on the theme My Proud Region at SD Negeri Galunggung. The research employed a quantitative approach with a one-group pretest–posttest experimental design. The sample consisted of 24 students selected through cluster random sampling. The instrument, an essay test, was validated by experts and tested for reliability, yielding a Cronbach’s Alpha of 0.86. Data were analyzed using paired-sample t-tests and N-Gain analysis. The findings revealed a significant improvement in students’ understanding, with the average pretest score rising from 53.75 to 86.67 in the posttest, and an N-Gain score of 0.75 in the high category. These results indicate that DDCT effectively enhances higher-order thinking skills, fosters active participation, and helps students connect Social Studies concepts to real-life contexts. The model also aligns with the goals of the Merdeka Curriculum in developing 21st-century competencies. Nevertheless, this study has limitations, particularly the absence of a control group and its focus on a single school context, which restricts the generalizability of the findings. Further research using controlled experimental designs and involving more diverse school settings is recommended to strengthen these results.